Right ventricular systolic pressure response during exercise in adolescents born with atrial or ventricular septal defect - Möller, Thomas; Brun, Henrik; Fredriksen, Per Morten; Holmstrøm, Henrik; Peersen, Kari; Pettersen, Eirik; Grünig, Ekkehard; Mereles, Derliz; Thaulow, Erik (The American journal of cardiology, 2010)
Our study investigated the abnormal right ventricular systolic pressure response (RVPR) in young patients with isolated atrial septal defect (ASD) or ventricular septal defect (VSD). An abnormal RVPR >50 mm Hg during exercise has been identified as a precursor of pulmonary artery hypertension. The present study included a population-based selection of 44 patients (age 13 to 25 years) with either isolated VSD (n = 27) or ASD (n = 17) and without right ventricular outflow tract obstruction. Of the 44 defects, 28 had been surgically closed (17 ASDs and 11 VSDs); 16 minor VSDs were untreated. Cardiovascular exercise testing and echocardiography at rest and during exercise were performed for all patients and 88 healthy controls. The aerobic capacity was significantly reduced in all patient groups (open VSD, closed VSD, closed ASD). The measurements of right ventricular performance were significantly lower in patients with closed ASD or closed VSD compared to those of the controls and patients with open VSD. Finally, 5% of the controls, no patient with ASD, and 9 patients with VSD (33%), regardless of defect closure, had an abnormal RVPR during exercise. In conclusion, 1/3 of young patients with isolated VSD had an abnormal RVPR during exercise.